Cachexia: a nutritional syndrome?. Issue 4 (December 2015) - Anker, Stefan D.; Morley, John E
Abstract: Cachexia leads to nutritional deficits including anorexia and loss of fat and muscle mass. In persons with precachexia or early cachexia, for example, old persons with weight loss and chronic obstructive pulmonary disease, there is strong evidence that nutritional support improves outcomes. Limited evidence suggests that this may be true for heart failure and chronic kidney disease. The evidence for nutritional support in refractory cachexia is, not surprisingly, less dramatic. It would appear that early in the cachectic process, nutrition, coupled with exercise, may be an important therapeutic approach.